1994
DOI: 10.3354/meps115151
|View full text |Cite
|
Sign up to set email alerts
|

Structure and production of the benthic macroinvertebrate community in a shallow lagoon in the Bay of Cadiz

Abstract: The composition and distribution of the benthic macroinvertebrate community in a lagoon fish-pond system in the Bay of Cadiz. Spain, were studied by taking monthly samples at 4 sites during 1991. A total of 29 macroinvertebrate species, representing 16 orders. were identified. Gastropods, amphipods and chironomid larvae dominated the macrofauna in term of numbers of individuals, while in biomass terms gastropods, bivalves and polychaetes were dominant. The diversity (H') and evenness (J') indices of this com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
42
1
11

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 21 publications
8
42
1
11
Order By: Relevance
“…The results of the number and density of species and diversity indices revealed the same seasonal distribution pattern of the molluscan community, ranging from rich community in the summer to an poorer one in winter, apparently due to a "dystrophic crisis" episode occurring during summer. Similar seasonal patterns have also been observed in other studies (Amanieu et al, 1977;Gravina et al, 1989;Arias and Drake, 1994;Dounas and Koutsoubas, 1996;Lardicci et al, 1997). This study gives for the first time a list of mollusc species hosted by the peculiar habitat of Hammamet Marina, which can be considered as far from definitively complete.…”
Section: Discussionsupporting
confidence: 88%
“…The results of the number and density of species and diversity indices revealed the same seasonal distribution pattern of the molluscan community, ranging from rich community in the summer to an poorer one in winter, apparently due to a "dystrophic crisis" episode occurring during summer. Similar seasonal patterns have also been observed in other studies (Amanieu et al, 1977;Gravina et al, 1989;Arias and Drake, 1994;Dounas and Koutsoubas, 1996;Lardicci et al, 1997). This study gives for the first time a list of mollusc species hosted by the peculiar habitat of Hammamet Marina, which can be considered as far from definitively complete.…”
Section: Discussionsupporting
confidence: 88%
“…In general, temperature increases can be a stimulus for spawning in polychaetes, though temperature decreases may have a similar effect (ARIAS & DRAKE 1995). The continuous reproduction observed in this study was also reported in a population of Scolelepis goodbodyi from Barequeçaba Beach, in São Paulo (MACCORD & AMARAL 2007).…”
Section: Discussionsupporting
confidence: 76%
“…Muus 1967;Scalera Liaci et al 1982;Cottiglia et al 1983aCottiglia et al , 1983bKhoury 1984;Mauge´1986;Kevrekidis et al 1990). The increased number of macroalgae during summer and autumn, when both epibenthic predators are most abundant and their feeding activity, especially in summer, is probably high, may offer macrobenthic invertebrates a refuge from predation (Arias and Drake 1994).…”
Section: Discussionmentioning
confidence: 99%